SKILL-BASED MADRASAH MANAGEMENT IN INCREASING STUDENT INDEPENDENCE AT MADRASAH MA AL-IRSYAD GAJAH - Agus Supriyadi; Arfandi Arfandi; Abdul Muís; Muna Khoirun Nafi (LP2M Universitas Ibrahimy, 2023)
Madrasah Aliyah Al-Irsyad in Demak district in Central Java is one of the madrasahs that conducts skills-based programs. Good educational administration may be an essential component of the school. School management may be effective when it combines numerous traits, such as organizational leadership, curriculum leadership, supervisory leadership, and management. It is envisaged that establishing a skills program would help students develop their human resources while also improving the quality of education in general. Skills education that is well executed will become a particular attraction and will have value for the community to enrol their children in MA. Gajah al-Irsyad.